A Cross-Layer Framework for Efficient Streaming of H.264 Video over IEEE 802.11 Networks. (2nd July 2009) - Moid, Azfar; Fapojuwo, Abraham O.
Abstract : This paper presents a framework for reliable and efficient streaming of H.264 video over an IEEE 802.11-based wireless network. The framework relies on a cross-layer mechanism that jointly adapts the video transcoding parameters at the application layer and the video transmission parameters at the data-link layer to the network conditions defined by buffer length and wireless propagation channel. The effectiveness of the proposed framework is demonstrated through the transmission of three test video sequences ( Akiyo, Container, and Foreman ) having different degrees of motion over an IEEE802.11 wireless network. Simulation results show that the proposed cross-layer-based framework provides an enhancement of up to 3 dB in the video quality with a negligible increase (<5%) in the packet processing time. Hence, the proposed framework achieves a good balance in the tradeoff between video quality and packet processing time. The proposed framework, along with its performance results, provides valuable insights on the selection of network parameter values for efficient and reliable transmission of video applications in wireless networks.